Improved Resistive Plate Chambers for the upgrade of the CMS muon detector. Issue 1 (1st November 2022) - Samalan, A.; ,
Abstract : Several upgrades of the Resistive Plate Chamber (RPC) system of the Compact Muon Solenoid (CMS) experiment are currently being implemented to ensure a highly performing muon system during the upcoming High Luminosity phase of the Large Hadron Collider which will have an increased integrated luminosity of 3000 fb −1 . The expected experimental conditions in that period present a challenge for the entire CMS detection system. To extend the RPC coverage, an improved version of the already existing RPCs will be installed in the forward region of the 3rd and 4th endcap disks. The current overall status of this CMS RPC upgrade project is presented.